RESEARCH AND COMMUNITY SERVICE MANAGEMENT INFORMATION SYSTEM AT P3-M UNIVERSITY OF YAPIS PAPUA - Salahudin Robo; Lasmaida Gultom; Sitti Nur Alam; Muhammad Riandi Widiyantoro (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Improving the quality of lecturers include in Tri Darma of University, they are: teaching, research and community service. These activities are fully managed by research and community service units or institutions in each university. University of Yapis Papua has a work unit that manages these activities, it called Pusat Penelitian dan Pengabdian Masyarakat (P3-M), where the process of managing research and community service activities is not yet fully integrated and well-documented. This study aims to create information system of activity management from P3-M unit at University of Yapis Papua. This information system will be used, the management of activities research and community service includes administrative data for submitting activity proposals, and reporting results. It hopes can be coordinated well. The methods were used waterfall as a system development method, Unifield Modeling Language (UML) for system design, and pieces method for problem analysis. The result of this study is produce a web-based information system with several menus that could help P3-M University of Yapis Papua.